Hordókészítés Salánkon: anyagok, eszközök, technológiák, termékek - Kész Barnabás; Кейс Борнобаш (Magyar Néprajzi Társaság, 2021)
Az alkalmas nyersanyagban bővelkedő, szőlő- és bortermeléséről híres Ugocsa egyik legmeghatározóbb háziipara a hordókészítés volt.1 A 20. század első felében a kádármesterség még összefüggő térséget ölelt fel az egykori Szernye-mocsár környékén Salánktól Szerednyéig. Ezt a Beregben végzett korábbi kutatások is alátámasztják. 1940-ben K. Kovács László például a Bereg-megyei Dercen hordókészítésének fázisait dokumentálta, fotósorozata a Néprajzi Múzeum fotótárában található.2 Beregújfaluból pedig közli Bodnár Kovács János kádármester hordóformájának fotóját, megjegyezve, hogy 1940-ben már ő az egyetlen, aki a településen hordókészítéssel foglalkozik.

Abstract. One of the most important handicrafts in Ugocsa and Bereg county famous for vineyards was barrel making. In the first half of the 20th century cooper’s craft around the Szernye marshland covered an extended area. Nowadays it is restricted to only one settlement, namely, Salánk (Шаланки/Salanki/ Shalanky), in western Ukraine, and its future is rather uncertain. The author in his article draws a parallel between tub- and barrel-making in Hungary and in Sub-Carpathia in Ukraine. Coopers in Salánk acquired the craft from their fathers or from each other and did not take a master’s exam. After the local barrel-producing firm had been liquidated they have worked in their own workshops at home, taking order. They do not prefer going to markets and fairs; it is usually the junior coopers who take their products to wine festivals. Coopers in Salánk usually make wine, vinegar and cabbage barrels, as well as tubs, wooden buckets for sauna and wooden planters. A special product from Salánk is the round or elliptic shaped little barrel for tables. Local coopers use almost exclusively pin oak (Quercus Palustris). Although they use machinery, but they set great store on their old manual tools and they name them with German technical terms. Terminology just as well as the process and technology of barrel making are mostly identical with those of the craft in Hungary, there are only some tools that are named differently. The barrel of Salánk some years ago was enlisted in the Hungarian Heritage Abroad Inventory. Despite this acknowledgement, the survival of this traditional craft that had a determinative role in this micro-region is endangered due to a limited access to raw material as a result of tinder mining.
Barrel-making in Salánk: Materials, tools, technologies and products
Keywords: Salánk; hordókészítés; kádármesterség